International Economics / Theory and Policy - Krugman Paul; Obstfeld Maurice (Pearson International Edition, 2006)
Introduction, International Trade Theory, World Trade: An Overview, The Standard Trade Model, International Factor Movements, International Trade Policy, The Instruments of Trade Policy, The Political Economy of Trade Policy, Trade Policy in Developing Countries, Controversies in Trade Policy, Exchange Rates and Open-Economy, Natioan lncome Accounting and the Balance of Payments, Money and Interest Rates and Exchange Rates, Price Levels and thje Exchange Rate in the Long Run, Output and the Exchange Rate in the Short Run, International Macroeconomic Policy, Macroeconomic Policy and Coordination Under Floating Exchange Rates, Optimum Currency Areas and the European Experience, The Global Capital Market: Performance and Policy Problems, Developing Countries: Growth and Crisis and Reform, Mathematical Postscripts, Credits, Index.